Estimation of efficiency of counteraction to photographic reconnaissance and video recording by the method of infrared hiding - Kukush, V.D.; Oleynikov, A.N.; Dibrova N.А. (Radiotekhnika, 2018)
The photographic reconnaissance is the most widespread and effective method of getting information by the visual-optical channel. Reconnaissance facilities such as video- and photo cameras are accessible, multifunction devices which provide an opportunity to obtain information both in visible and infrared range of radiation. Active and passive methods are used for counteraction to the photographic reconnaissance. One of the active methods is the method of the infrared hiding. It is based on the deterioration of the contrast of the photographed object due to light interference into the lens. The article shows results of the experimental estimation of the infrared hiding method efficiency applied against typical set of the photographic reconnaissance facilities.